2012
DOI: 10.2135/cropsci2011.04.0214
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Quantitative Trait Loci Mapping for Gibberella Ear Rot Resistance and Reduced Deoxynivalenol Contamination across Connected Maize Populations

Abstract: Gibberella ear rot (GER) of maize (Zea mays L.) caused by Fusarium graminearum Schwabe leads to yield loss and contamination with deoxynivalenol (DON), the most commonly detected mycotoxin. To enhance the efficiency of marker-assisted selection (MAS), it is necessary to identify quantitative trait loci (QTL), which are effective across different genetic backgrounds. The objectives of the present study were to (i) map QTL for GER resistance and reduced DQN contamination, (ii) examine the congruency of QTL ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 39 publications
4
36
0
Order By: Relevance
“…Two NIRS measurements per plot were taken with a NIRSystems 6500 spectrometer (FOSS NIRSystems, Inc. Silver Spring, MD, USA) and averaged. A NIRS calibration equation, which was developed by Bolduan et al (2009b) and validated by Martin et al (2011b), was applied to the spectral data to predict DON concentrations on the natural log scale for each sample using the WinISI III software (Infrasoft International LLC, State College, PA, USA).…”
Section: Trait Recordingmentioning
confidence: 99%
“…Two NIRS measurements per plot were taken with a NIRSystems 6500 spectrometer (FOSS NIRSystems, Inc. Silver Spring, MD, USA) and averaged. A NIRS calibration equation, which was developed by Bolduan et al (2009b) and validated by Martin et al (2011b), was applied to the spectral data to predict DON concentrations on the natural log scale for each sample using the WinISI III software (Infrasoft International LLC, State College, PA, USA).…”
Section: Trait Recordingmentioning
confidence: 99%
“…However, a marker assisted selection approach is advisable to accelerate genetic progress (RobertsonHoyt et al 2006b). Several QTLs for ear rot resistance have been mapped in different maize populations from Africa, America, Asia and Europe (Pérez Brito et al 2001;Liakat Ali et al 2005;Robertson-Hoyt et al 2006b;Zhang et al 2007;Ding et al 2008;Rey et al 2009;Martin et al 2012;Tembo et al 2014). In Argentina, QTLs for ear rot resistance were reported in an inbred that had been released from Stiff Stalk Synthetic (Rey et al 2009) but there is scarce information on QTLs from inbreds released from ancient local germplasm.…”
Section: Introductionmentioning
confidence: 99%
“…This result corroborated that obtained by Robertson et al (2006), who obtained a heritability estimate of 80% for the trait of resistance to F. verticillioides. Likewise, resistance to ear rot caused by F. graminearum verified by Martin et al (2012) also showed high heritability (h 2 = 0.79).…”
Section: Resultsmentioning
confidence: 94%
“…In the literature, heritability of resistance to the symptoms caused by Fusarium spp and manifested in kernels is estimated to be of medium to high magnitude (Robertson et al, 2006;Martin et al, 2012), showing that there is correspondence between the phenotypic value and genetic value, which facilitates gain from selection. However, genetic control and the mechanisms of plant resistance to this fungus have not yet been fully explained.…”
Section: Introductionmentioning
confidence: 99%